2022
DOI: 10.3390/photonics9060387
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of the Optical Properties of TMDC/Graphene Heterostructures

Abstract: The transition-metal dichalcogenide (TMDC) in the family of MX2 (M=Mo,W; X=S,Se) and the graphene (Gr) monolayer are an atomically thin semiconductor and a semimetal, respectively. The monolayer MX2 has been discovered as a new class of semiconductors for electronics and optoelectronics applications. Because of the hexagonal lattice structure of both materials, MX2 and Gr are often combined with each other to generate van der Waals heterostructures. Here, the MX2/Gr heterostructures are investigated theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…It is found that, due to van derWaals interactions, the Dirac point in MX2/Gr hybrids opens a small gap that is minimum for WSe2/Gr. The lattice mismatch ratio of WSe2/Gr is also reported to be the smallest one at 0.01% 49 …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…It is found that, due to van derWaals interactions, the Dirac point in MX2/Gr hybrids opens a small gap that is minimum for WSe2/Gr. The lattice mismatch ratio of WSe2/Gr is also reported to be the smallest one at 0.01% 49 …”
Section: Resultsmentioning
confidence: 94%
“…In the MoS2/graphene heterostructure, the electron transfer from MoS2 to graphene is observed, whereas in the WSe2/graphene heterostructure, the electron transfer from graphene to WSe2 is observed. The interlayer process can also be modulated by laser intensity, which enables photo-induced doping on graphene and optically tunable electrical characteristics of graphene 49 . Meanwhile, stacking of MoS2 on graphene usually leads to a much larger shift of the graphene G band, compared with the case of graphene on MoS2 39 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The refractive index effects are dominated by the real part of dielectric function, [ 34 ] which is observed by comparing the plots of dielectric function, as shown in Figure 5a–f, with the plots of refractive index (Figure 7a–f). The refractive index plot shows a similar behavior with the increase of photon energy as that of dielectric constant.…”
Section: Resultsmentioning
confidence: 98%